Children's preferences concerning the physical appearance of dental injectors - (:unkn) unknown (My University, 2006)
PURPOSE: This pilot study was carried out to assess how the physical appearance of dental injectors influenced children's choice. METHODS: The study group consisted of 34 randomly selected children (17 boys, 17 girls) between the ages of 7 and 11 (mean age=8.6 +/- 1.4), who had been registered for treatment at the School of Dentistry, Marmara University. A combination of tests-the Children's Fear Survey Schedule-Dental Subscale (CFSS-DS), Venham Picture Test (VPT), and facial image scale (FIS)-were used to assess the multi-dimensional character of children's dental anxiety. Dental injectors (Wand, Citoject, traditional metal injector MI], and plastic injector PI]) were displayed on a tray and introduced to the children. The children were asked to consider which injectors they would choose "if their tooth had to be put to sleep," and their preferences were noted starting with their first choice. RESULTS: The children's first choice was: (1) the Wand (56%); (2) PI (29%); (3) Citoject (12%); and (4) MI (3%). The anxious children (n= 13) preferred the Wand with significantly higher ratings (Wand=84%; Citoject=8%; MI=8%; PI=0%). CONCLUSION: The physical appearance of dental injectors is important to children and even more important for children who are anxious.
Keywords: Female; Humans; Male; Child; Attitude to Health; Equipment Design; Alloys; Pilot Projects; Patient Satisfaction; Dental Anxiety; Injections; Anesthesia, Local; Plastics; Anesthesia, Dental; Injections, Jet; Syringes